Comparative Effectiveness of Two Problem-Solving Teaching Approaches on Senior Secondary School Students’ Attitude to and Achievement in Practical Chemistry (2015)
It has been observed that many secondary school students in Nigerian perform poorly in chemistry. This may be attributed to the teaching methods used by their teachers as well as inadequate provision of practical materials and activities. Very often, students only observe experiments, copy notes and draw diagrams during chemistry lessons. Studies have revealed that students do not actively and effectively take part in practical chemistry exercises and this may be part of the reasons for their poor performance in the subject. This study, therefore examined the extent to which Laboratory Problem-Solving Model (LAPSOM) and Hands-on, Minds-on Problem-Solving Model (HAMPSOM) improved students’ attitude to and achievement in practical chemistry. It further determined the moderating effects of chemistry process skills and class size. A pretest-posttest, control group quasi experimental design with a 3 x 2 x 2 factorial matrix was used. From the eight educational zones in Oyo State, three were randomly selected from Ibadan and Oyo towns. Three Local Government Areas (LGAs) were chosen based on the geographical location from each of the selected zones. Nine public senior secondary schools were randomly chosen from the selected LGAs. Nine intact classes of 359 students participated and were assigned to LAPSOM, HAMPSOM and control groups. Treatment lasted six weeks. The instruments used were: Chemistry Achievement Test (r=0.79), Students’ Attitude to Practical Chemistry Scale (r=0.85), Chemistry Process Skills Rating Scale (r=0.78). LAPSOM, HAMPSOM, and Conventional Method. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using ANCOVA. There was a significant main effect of the treatments on students’ achievement in practical chemistry (F(2,346)=13.03, η2=0.070, R2=.176). Students exposed to HAMPSOM performed better (x=20.02) than those in LAPSOM (x=18.64) and the control group (x=15.09). There was no significant main effect of the treatments on students’ attitude to practical chemistry. Both high and low chemistry process skills had significant effect on students’ achievement in practical chemistry (F(1,346)=10.15, η2=0.029, R2=.176). Students exposed to HAMPSOM with high skill performed best (x=47.16) followed by those exposed to LAPSOM (x=40.79) and control (x= 40.29). Chemistry process skills had no significant effect on students’ attitude to practical chemistry. Large and small class sizes had significant effect on students’ achievement in practical chemistry (F(1,346)=14.54, η2=0.04, R2=.176) but students in small class performed better (x=19.43) than those in large class (x=16.38). There was no effect on students’ attitude to practical chemistry, even though students in large class had better attitude (x=92.17) than those in small class (x=90.65). There was a significant interaction effect of treatments and chemistry process skills on students’ attitude to practical chemistry (F(2,346)=3.31, η2=0.019, R2=.032) and also students’ achievement in practical chemistry (F(2,346)=5.11, η2=0.029, R2=.176). The other two-way and three-way interactions had no significant effects on both. Hands-on and Minds-on problem-solving approach had greater impact than Laboratory problem-solving approach on students’ attitude to and achievement in chemistry. Teachers should therefore employ Hands-on and Minds-on problem-solving approach in teaching chemistry.